2021
DOI: 10.3390/ijms222111967
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic Therapy for Cerebral Ischemia-Reperfusion Injury

Abstract: Ischemic stroke is one of the leading causes of death, and even timely treatment can result in severe disabilities. Reperfusion of the ischemic stroke region and restoration of the blood supply often lead to a series of cellular and biochemical consequences, including generation of reactive oxygen species (ROS), expression of inflammatory cytokines, inflammation, and cerebral cell damage, which is collectively called cerebral ischemia-reperfusion (IR) injury. Since ROS and inflammatory cytokines are involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…Tissue plasminogen activator (tPA) is the only supported pharmacological thrombolytic medicine because of its ability to recanalize arteries and improve clinical outcomes ( National Institute of Neurological Disorders and Stroke rt-PA Stroke Study Group, 1995 ). Restoration of the blood supply into the ischemic stroke region may also induce cerebral ischemia/reperfusion injury (CIRI) ( Lim et al, 2021 ). Moreover, only a shortage of patients with CIS benefits from tPA treatment due to the narrow therapeutic time window, tendency to transform into a hemorrhage, and other side effects ( Bansal et al, 2013 ; Yeo et al, 2013 ; Bhaskar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue plasminogen activator (tPA) is the only supported pharmacological thrombolytic medicine because of its ability to recanalize arteries and improve clinical outcomes ( National Institute of Neurological Disorders and Stroke rt-PA Stroke Study Group, 1995 ). Restoration of the blood supply into the ischemic stroke region may also induce cerebral ischemia/reperfusion injury (CIRI) ( Lim et al, 2021 ). Moreover, only a shortage of patients with CIS benefits from tPA treatment due to the narrow therapeutic time window, tendency to transform into a hemorrhage, and other side effects ( Bansal et al, 2013 ; Yeo et al, 2013 ; Bhaskar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of additional clinical relevance, senolytics applied to organ donors prior to procurement, prolonged the survival of old cardiac allografts beyond that of young donors ( 125 ). Most recently, experimental models have indicated that IRI itself can induce senescence and that senolytics have the potential to ameliorate this injury ( 126 128 ). Notably, senolytics have been tested before in patients with idiopathic pulmonary fibrosis.…”
Section: Impact Of Aging On Ischemia Reperfusion Injurymentioning
confidence: 99%
“…Evidence suggests that thrombolytic therapy effectively treats ischemic stroke and decreases morbidity and mortality when timely provided ( Man et al, 2020 ). Ischemia and reperfusion result in several cellular and biochemical consequences, including intracellular Ca 2+ overload, excitatory amino acid poisoning, inflammatory response, oxidative damage, apoptosis, and so forth ( Lo et al, 2003 ; Khatri et al, 2012 ; Radak et al, 2017 ; Lian et al, 2020 ; Lim et al, 2021 ). Novel treatments are urgently needed to prevent and treat the cerebral ischemia-reperfusion (I/R) injury.…”
Section: Effects Of Tetramethylpyrazine On Central Nervous System Dis...mentioning
confidence: 99%